The Impact of Ancillary HIV Services in Improving Retention in Care and How They Can Be Prioritized and Allocated to Maximize Outcomes - Niyang, Piring’ar Mercy; Gobir, Ibrahim; Musa, Joy; Mwantiyi, Bitrus; Zubayr, Bashir; Egigogo, Yakubu Raji; Olatunbosun, Kolawole; Usha, Terso; Ikpeme, Mabel; Gado, Pamela; Igboelina, Onyeka; Obiora-Okafor, Chika; et al. (British Journal of Healthcare and Medical Research, 2025)
Background: Community programs play a vital role in providing ancillary HIV services, including prevention, treatment, and support. This scoping review aims to synthesize evidence on the impact of ancillary services on retention in care and identify strategies to prioritize and allocate resources effectively. Methods: A comprehensive search of peer-reviewed literature published in the last decade was conducted. Fifteen studies were selected based on predetermined inclusion criteria, and data were extracted and analyzed to identify key themes and findings. Results: Community programs offering a range of services, including HIV testing and counseling, ART provision and follow-up, nutrition support, psychosocial support, and financial support, were found to positively impact care retention. These programs increased access to ART, improved adherence, enhanced treatment outcomes, and reduced loss to follow-up. A patient-centered approach to chronic disease care was also identified as an effective strategy to empower patients to manage their condition. Conclusion: This scoping review highlights the importance of community programs in improving retention in care and treatment outcomes for individuals living with HIV. Decentralizing HIV services through community-based initiatives is a promising strategy to increase access to essential health services. Policymakers, managers, and healthcare providers should recognize the value of community programs and work to enhance and support their role in the response to the HIV epidemic.